BPRS Era Society 5.0: Strategi Digital Inklusif untuk Akselerasi Keuangan Hijau dan Inovatif Syariah di Indonesia - Sudarmanto, Eko; Mahdi, Fadilla Muhammad; Rosidawaty, Rosidawaty; Istiasih, Shitny Dwi; Sasmita, Djenni (ITB AAS INDONESIA Surakarta, 2025)
Digital transformation has become an imperative for Islamic Rural Banks (BPRS) in responding to the challenges and opportunities of the Society 5.0 era, where technology and human values are seamlessly integrated. This study aims to identify inclusive digital strategies that BPRS can adopt to accelerate the development of green and innovative finance based on Sharia principles. Employing a qualitative approach through literature review, this research examines recent scholarly works, Sharia regulations, financial authority reports, and government policies related to digitalization and sustainable finance. The findings reveal that BPRS digitalization grounded in financial inclusion and maqashid shariah holds strategic potential in promoting green financing, empowering Muslim communities, and enhancing financial literacy. Nevertheless, structural challenges, such as limited digital infrastructure and regulations that are not yet fully adaptive, remain significant barriers. This study recommends strengthening cross-sector collaboration, developing digital products rooted in Islamic values, and formulating policies that foster Sharia-compliant financial innovation with an environmentally friendly orientation as strategic directions for the future.